Spherification as a prospective technique of product production at restaurants - Dotsenko, Viktor; Arpul (Oleksiichuk), Oksana; Tyshchenko (Usatiuk), Olena; Bloshchinska (Dudkina), Olena (My University, 2012)
The paper presents the results of practical researches of spherification as an innovative technique of molecular gastronomy which enables to provide the traditional dishes and culinary products the unusual appearance without changing their nutritional and biological value.
Keywords: spherification; molecular technologies; sodium alginate; calcium chloride; spheres; daily requirement; organoleptic evaluation; молекулярні технології; альгінати; хлорид кальцію; сфери; добова потреба; органолептична оцінка; кафедра готельно-ресторанної справи